Kekuatan Geser Semen Ionomer Kaca pada Dentin Gigi Sulung setelah Aplikasi Kondisioner dengan Durasi Berbeda - Suzanna Sungkar; Margaretha Suharsini; Hendrarlin Soenawan (Faculty of Dentistry, Universitas Indonesia, 2015)
The bond strength between glass ionomer and tooth structure can be improved with application of conditioner on enamel or dentin surface to remove the smear layer. The bond strength can be measured with shear bond strength testing. This study aimed to determine the difference of shear bond strength of glass ionomer cement to primary teeth dentine after conditioner application for 10", 20" and 30". Twenty seven primary mandibular incisors were randomly divided into 3 groups that were subjected to application of 10% polyacrylic acid conditioner (Dentin conditioner, GC) for 10", 20" and 30", and restoration with glass ionomer cement (Fuji IX, GP, GC). The specimens were kept in an incubator at 37ºC for 24 hours. Shear bond strength test was done by using Universal Testing Machine Shimazu AG-5000 with 50 kgf load and crosshead speed of 0.5 mm/min. Anova was used statistical evaluation. Although the results showed no statistically significant differences in the shear bond strength of the glass ionomer cement between the test groups (p>0.05), the mean bond strength decreased with increasing duration of conditioner application, so that highest mean bond strength was obtained at 10" application.